The Core of an Economy with a Measure Space of Economic Agents - Hildenbrand, W. (Review of Economic Studies, 1968)
Journal Article The Core of an Economy with a Measure Space of Economic Agents Get access W. Hildenbrand W. Hildenbrand University of California, Berkeley, U.S.A., Studiengruppe für Systemforschung, Heidelberg, Germany Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 4, October 1968, Pages 443–452, https://doi.org/10.2307/2296771 Published: 01 October 1968